2020
DOI: 10.18203/2320-1770.ijrcog20204935
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum hormone profile and semen quality of infertile males in and around Chennai

Abstract: Background: The infertility rate in India has also increased gradually along with population growth. Based on the geographic, the prevalence of male infertility varies. It is noticed that around the world 60–80 million couples with infertility problem every year. The aim of the study was to assess the correlation between the serum hormones and semen quality in infertile males.Methods: This research study was conducted in 60 infertile males aged from 20–50 years who reported at the Department of Andrology, Kanm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Palani et al concluded that serum TSH, FSH, LH and PRL show a negative correlation but testosterone level shows a positive correlation with semen parameters. 11 Osadchuk et al found significant association of serum LH, FSH and inhibin-B levels with sperm concentration and progressive sperm motility. 12 Our study found serum FSH level to be associated with sperm count, concentration and total motility, but not with progressive motility.…”
Section: Discussionmentioning
confidence: 99%
“…Palani et al concluded that serum TSH, FSH, LH and PRL show a negative correlation but testosterone level shows a positive correlation with semen parameters. 11 Osadchuk et al found significant association of serum LH, FSH and inhibin-B levels with sperm concentration and progressive sperm motility. 12 Our study found serum FSH level to be associated with sperm count, concentration and total motility, but not with progressive motility.…”
Section: Discussionmentioning
confidence: 99%